Composite diaphragm as well as preparation method and application thereof
By adopting a composite separator structure in the lithium-ion battery separator, combining the solid electrolyte layer and the inorganic ceramic layer, the problem of high heat shrinkage in the existing separator at high temperatures is solved, and the battery's efficient ion transmission, thermal stability and safety performance are improved.
Patent Information
- Application Number
- CN202411940597.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-18
AI Technical Summary
The existing lithium-ion battery separators have a high heat shrinkage rate at high temperatures, which makes it difficult to support the ceramic coating, which may cause short circuits of the positive and negative electrode materials, affecting the safety and rate performance of the battery.
A composite separator structure is adopted, including a base film, a solid electrolyte layer and an inorganic ceramic layer. The solid electrolyte layer assists ion transport. The inorganic ceramic layer has excellent thermal stability and shrinkage resistance, supporting the maintenance of the separator structure at high temperatures.
It significantly reduces the internal resistance of the battery, improves the rate performance and safety performance of the battery, and ensures the thermal stability and mechanical properties of the diaphragm at high temperatures.
Smart Images

Figure CN119651062A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials and relates to a composite diaphragm and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, good cycle performance, long service life, low self-discharge, and no memory effect. They are gradually occupying a larger application market in energy storage, power batteries, and 3C electronics, and have broad application prospects.
[0003] As one of the core components of lithium-ion batteries, lithium-ion battery separators play the role of isolating positive and negative electrodes, electronic insulation, and conducting lithium ions. The characteristics and quality of the separator seriously affect the safety performance, rate performance, cycle life and basic electrical performance of the battery. Surface modification of the separator is one of the important means to achieve high-performance lithium-ion batteries.
[0004] Existing diaphragms usually adopt a structure of base film plus coating. The selection and application of coating materials have a significant impact on the safety performance of secondary batteries, including ceramic coatings, which are usually made of materials such as aluminum oxide, titanium oxide or zirconium oxide. Ceramic coatings have high melting points and good chemical stability, which can effectively improve the safety performance of secondary batteries. Among them, the ceramic coating mainly plays the role of skeleton support, but because the base film of the ceramic diaphragm is mostly a polyolefin base film, it has a large thermal shrinkage rate at high temperature, making it difficult for the ceramic coating to fully support the diaphragm without deformation, resulting in direct contact between the positive and negative electrode materials and short circuit, resulting in insufficient safety of the secondary battery.
[0005] CN112952296A discloses an ion membrane and its preparation method as well as a semi-solid electrolyte battery, in which solid electrolyte materials such as LATP that can transmit lithium ions are coated on the surface of a polyolefin microporous diaphragm, thereby improving the ionic conductivity of the diaphragm and reducing the internal resistance of the battery. However, for liquid batteries or solid-liquid hybrid batteries, the transmission capacity of lithium ions in the electrolyte is much greater than that in the solid electrolyte bulk phase and grain boundaries, and the improvement in the battery charging performance in actual use is not obvious. On the other hand, a simple solid electrolyte coating diaphragm cannot improve the cycle life and safety of lithium batteries.
[0006] CN110859053A discloses a method for preparing an organic / inorganic composite diaphragm, which is prepared by using a mixture of a fluorine or acrylic resin polymer and inorganic particles to prepare a coating slurry, and coating the surface of a polyolefin microporous diaphragm. The composite diaphragm has good liquid absorption / retention ability, strong peeling resistance, and high adhesion to positive and negative electrodes. However, the use of high-particle-size inorganic particles and low-particle-size inorganic particles will cause the inorganic particles in the coating layer to form a relatively dense accumulation form, affecting the rate performance of the battery.
[0007] The composite diaphragm described in the above solution is difficult to achieve both stability and safety performance, and the rate performance of the battery will be reduced due to the influence of the materials in the coating. Summary of the invention
[0008] The object of the present invention is to provide a composite diaphragm and a preparation method and application thereof. The composite diaphragm of the present invention can improve the ion transmission efficiency of the battery, and has excellent thermal stability and safety performance, can significantly reduce the internal resistance of the battery, and improve the rate performance of the battery.
[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a composite diaphragm, comprising a base membrane and a solid electrolyte layer and an inorganic ceramic layer respectively disposed on both side surfaces of the base membrane.
[0011] Different types of composite layers are arranged on both sides of the composite diaphragm described in the present invention. The solid electrolyte layer can assist ion transport. The inorganic ceramic layer has excellent thermal stability and dimensional integrity at high temperatures, and plays a supporting role in maintaining the diaphragm structure at high temperatures. The inorganic ceramic layer has greatly improved shrinkage resistance, and has better mechanical properties and safety.
[0012] Preferably, the base film comprises a nonwoven fabric.
[0013] Preferably, the structure of the base film includes a three-dimensional structure.
[0014] Preferably, the three-dimensional structure is formed by cross-linking linear polyethylene terephthalate (PET) cellulose.
[0015] Preferably, the diameter of the linear PET cellulose is 0.2 μm to 0.8 μm, for example, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm or 0.8 μm, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0016] The non-woven fabric material used in the present invention has the advantages of high temperature resistance and high porosity. In addition, due to its three-dimensional pore structure, it can effectively avoid short circuits caused by needle puncture and improve the liquid retention rate. Its high porosity can provide more ion channels, reduce DCR, and support high-rate charge and discharge.
[0017] Preferably, the thickness of the base film is 10 μm to 20 μm, for example, 10 μm, 12 μm, 15 μm, 18 μm or 20 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] Preferably, the air permeability value of the base film is 15Sec / 100cc to 20Sec / 100cc, for example: 15Sec / 100cc, 16Sec / 100cc, 17Sec / 100cc, 18Sec / 100cc, 19Sec / 100cc or 20Sec / 100cc, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] Preferably, the material of the solid electrolyte layer includes solid electrolyte particles and a first binder;
[0020] Preferably, the solid electrolyte particles include lithium aluminum titanium phosphate (LATP);
[0021] Preferably, the mass ratio of the solid electrolyte particles to the first binder is (70-90):(10-30).
[0022] Preferably, the median particle size D50 of the LATP is 500 nm to 1500 nm, for example, 500 nm, 800 nm, 1000 nm, 1200 nm or 1500 nm, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0023] Preferably, the first binder comprises polyacrylate.
[0024] Preferably, the thickness of the solid electrolyte layer is 1 μm to 3 μm, for example, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] Preferably, a first glue coating layer is further provided on the side of the solid electrolyte layer away from the base membrane.
[0026] The present invention can decide whether to add the first coating layer or the second coating layer according to the battery design requirements, which helps to increase the hardness of the battery and inhibit cyclic deformation.
[0027] Preferably, the first coating layer includes a polymethyl methacrylate (PMMA) coating layer and / or a polyvinylidene fluoride (PVDF) coating layer.
[0028] Preferably, the thickness of the PMMA coating layer is 0.5 μm to 1.0 μm, for example, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1.0 μm, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, the thickness of the PVDF coating layer is 1 μm to 2 μm, for example, 1 μm, 1.2 μm, 1.5 μm, 1.8 μm or 2 μm, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0030] Preferably, the inorganic ceramic layer comprises inorganic ceramic particles and a second binder.
[0031] Preferably, the mass ratio of the inorganic ceramic particles to the second binder is (85-95):(5-15).
[0032] Preferably, the inorganic ceramic particles include alumina and / or boehmite ceramics.
[0033] Preferably, the second binder comprises polyacrylate.
[0034] Preferably, the thickness of the inorganic ceramic layer is 1 μm to 3 μm, for example, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0035] Preferably, a second glue coating layer is further provided on the side of the inorganic ceramic layer away from the base film.
[0036] Preferably, the second adhesive coating layer includes a PMMA adhesive coating layer and / or a PVDF adhesive coating layer.
[0037] Preferably, the thickness of the PMMA coating layer is 0.2 μm to 0.8 μm, for example, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm or 0.8 μm, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] Preferably, the thickness of the PVDF coating layer is 1 μm to 2 μm, for example, 1 μm, 1.2 μm, 1.5 μm, 1.8 μm or 2 μm, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0039] In a second aspect, the present invention provides a method for preparing the composite diaphragm as described in the first aspect, the preparation method comprising the following steps:
[0040] The solid electrolyte layer and the inorganic ceramic layer are respectively prepared on the surfaces of both sides of the base film by a wet coating process to obtain the composite diaphragm.
[0041] Preferably, after the solid electrolyte layer is prepared, a first glue layer is coated on the solid electrolyte layer.
[0042] Preferably, after the inorganic ceramic layer is prepared, a second glue coating layer is coated on the inorganic ceramic layer.
[0043] In a third aspect, the present invention provides a battery, wherein the battery comprises the composite separator as described in the first aspect.
[0044] Preferably, the battery comprises a positive electrode and a negative electrode arranged on both sides of the composite diaphragm, and an electrolyte is also arranged in the battery.
[0045] Preferably, the solid electrolyte layer of the composite separator is close to the positive electrode side.
[0046] Preferably, the inorganic ceramic layer of the composite separator is close to the negative electrode side.
[0047] Compared with the prior art, the present invention has the following beneficial effects:
[0048] (1) The composite diaphragm of the present invention can improve the ion transmission efficiency of the battery, and has excellent thermal stability and safety performance, can significantly reduce the internal resistance of the battery, and improve the rate performance of the battery.
[0049] (2) The composite diaphragm of the present invention has an MD thermal shrinkage of less than 3.0% and a TD thermal shrinkage of less than 1.2% at 130°C for 1 hour, a 3C / 0.2C discharge rate of more than 96.2%, a needle puncture pass rate of more than 70%, and a thickness expansion rate of less than 5.6% after 300 cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 It is a schematic diagram of the structure of the composite diaphragm provided in an embodiment of the present invention.
[0051] Among them, 1 is a non-woven fabric base film, 2 is a solid electrolyte layer, 3 is an inorganic ceramic layer, 4 is a first coating layer, and 5 is a second coating layer. DETAILED DESCRIPTION
[0052] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0053] Example 1
[0054] This embodiment provides a composite diaphragm. The structural schematic diagram of the composite diaphragm is as follows: Figure 1 As shown, the composite separator includes a non-woven fabric base film 1 with a three-dimensional structure composed of linear PET cellulose with a diameter of 0.5 μm, and the air permeability value of the non-woven fabric base film 1 is 18 Sec / 100 cc and the thickness is 15 μm;
[0055] A solid electrolyte layer 2 and an inorganic ceramic layer 3 are respectively arranged on both sides of the non-woven fabric base film 1;
[0056] The solid electrolyte layer 2 contains LATP and polyacrylate binder in a mass ratio of (70-90): (10:30), the median particle size D50 of the LATP is 800 nm, and the thickness of the solid electrolyte layer 2 is 2 μm;
[0057] The inorganic ceramic layer 3 contains aluminum oxide and polyacrylate binder in a mass ratio of (85-95): (5-15), and the thickness of the inorganic ceramic layer 3 is 2 μm;
[0058] A first adhesive layer 4 is further disposed on the side of the solid electrolyte layer 2 away from the non-woven fabric base film 1 . The first adhesive layer 4 is a PMMA adhesive layer with a thickness of 0.5 μm.
[0059] A second adhesive layer 5 is also disposed on the side of the inorganic ceramic layer 3 away from the non-woven fabric base film 1 . The second adhesive layer 5 is a PVDF adhesive layer with a thickness of 1.5 μm.
[0060] Example 2
[0061] This embodiment provides a composite diaphragm. The structural schematic diagram of the composite diaphragm is as follows: Figure 1 As shown, the composite diaphragm includes a non-woven fabric base film 1 with a three-dimensional structure composed of linear PET cellulose with a diameter of 0.2 μm, and the air permeability value of the non-woven fabric base film 1 is 20 Sec / 100 cc and the thickness is 10 μm;
[0062] A solid electrolyte layer 2 and an inorganic ceramic layer 3 are respectively disposed on both sides of the non-woven fabric base film 1;
[0063] The solid electrolyte layer 2 contains LATP and polyacrylate binder in a mass ratio of 90:10, the median particle size D50 of the LATP is 500 nm, and the thickness of the solid electrolyte layer 2 is 1 μm;
[0064] The inorganic ceramic layer 3 contains boehmite ceramic particles and polyacrylate binder in a mass ratio of 95:5, and the thickness of the inorganic ceramic layer 3 is 1 μm;
[0065] A first adhesive layer 4 is further disposed on the side of the solid electrolyte layer 2 away from the non-woven fabric base film 1 . The first adhesive layer 4 is a PMMA adhesive layer with a thickness of 0.5 μm.
[0066] A second adhesive layer 5 is also disposed on the side of the inorganic ceramic layer 3 away from the non-woven fabric base film 1 . The second adhesive layer 5 is a PMMA adhesive layer with a thickness of 0.5 μm.
[0067] Example 3
[0068] This embodiment provides a composite diaphragm. The structural schematic diagram of the composite diaphragm is as follows: Figure 1 As shown, the composite diaphragm includes a non-woven fabric base film 1 with a three-dimensional structure composed of linear PET cellulose with a diameter of 0.8 μm, and the air permeability value of the non-woven fabric base film 1 is 20 Sec / 100 cc and the thickness is 20 μm;
[0069] A solid electrolyte layer 2 and an inorganic ceramic layer 3 are respectively disposed on both sides of the non-woven fabric base film 1;
[0070] The solid electrolyte layer 2 contains LATP and polyacrylate binder in a mass ratio of 90:10, the median particle size D50 of the LATP is 1500nm, and the thickness of the solid electrolyte layer 2 is 3μm;
[0071] The inorganic ceramic layer 3 contains aluminum oxide and polyacrylate binder in a mass ratio of 95:5, and the thickness of the inorganic ceramic layer 3 is 3 μm;
[0072] A first adhesive layer 4 is also disposed on the side of the solid electrolyte layer 2 away from the non-woven fabric base film 1 . The first adhesive layer 4 is a PVDF adhesive layer with a thickness of 1 μm.
[0073] A second adhesive layer 5 is also disposed on the side of the inorganic ceramic layer 3 away from the non-woven fabric base film 1 . The second adhesive layer 5 is a PVDF adhesive layer with a thickness of 2 μm.
[0074] Example 4
[0075] The only difference between this embodiment and the first embodiment is that the thickness of the solid electrolyte layer 2 is 0.5 μm, and the other conditions and parameters are exactly the same as those of the first embodiment.
[0076] Example 5
[0077] The only difference between this embodiment and the first embodiment is that the thickness of the solid electrolyte layer 2 is 4 μm, and the other conditions and parameters are exactly the same as those of the first embodiment.
[0078] Example 6
[0079] The only difference between this embodiment and the first embodiment is that the thickness of the inorganic ceramic layer 3 is 0.5 μm, and the other conditions and parameters are exactly the same as those of the first embodiment.
[0080] Example 7
[0081] The only difference between this embodiment and the first embodiment is that the thickness of the inorganic ceramic layer 3 is 4 μm, and the other conditions and parameters are exactly the same as those of the first embodiment.
[0082] Example 8
[0083] The only difference between this embodiment and the first embodiment is that the first adhesive layer 4 is not provided, and the other conditions and parameters are exactly the same as those of the first embodiment.
[0084] Example 9
[0085] The only difference between this embodiment and the first embodiment is that the second adhesive layer 5 is not provided, and the other conditions and parameters are exactly the same as those of the first embodiment.
[0086] Example 10
[0087] The only difference between this embodiment and embodiment 1 is that the non-woven fabric is replaced with polyethylene (PE), and the other conditions and parameters are exactly the same as those in embodiment 1.
[0088] Comparative Example 1
[0089] The only difference between this comparative example and Example 1 is that the LATP solid electrolyte layer and the PMMA coating layer are only provided on one side of the non-woven fabric base film 1, which faces the positive electrode side, and the alumina inorganic ceramic coating and the PVDF coating layer are not provided on the other side of the base film. Other conditions and parameters are exactly the same as those in Example 1.
[0090] Comparative Example 2
[0091] The only difference between this comparative example and Example 1 is that an alumina inorganic ceramic layer and a PVDF coating layer are provided only on one side of the non-woven fabric base membrane 1, which faces the negative electrode side, and no LATP solid electrolyte layer and PMMA coating layer are provided on the other side of the base membrane. Other conditions and parameters are exactly the same as those in Example 1.
[0092] Performance Test:
[0093] The composite diaphragms prepared in the embodiment and the comparative example were respectively subjected to air permeability test and 130°C 1h heat shrinkage test, and the composite diaphragms were used to assemble lithium batteries. The battery structure was a lithium cobalt oxide / SiC500 soft pack battery, with the solid electrolyte layer facing the positive electrode side and the inorganic ceramic layer facing the negative electrode side. After the steps of liquid injection, formation, and volume separation, the lithium battery prepared above was subjected to electrochemical tests and safety performance tests, respectively. The test methods are as follows:
[0094] Rate discharge: At room temperature, charge at 0.5C constant current to full charge voltage, then charge at constant voltage to current ≤0.025C; then discharge at 0.2C current to 3.0V cut-off discharge capacity (cycle 3 weeks, select the largest discharge capacity); At room temperature, charge at 0.5C constant current to full charge voltage, then charge at constant voltage to current ≤0.025C; then discharge at 3C current to 3.0V cut-off discharge capacity (cycle 3 weeks, select the largest discharge capacity). And calculate the 3C / 0.2C discharge rate.
[0095] Needle puncture test: Use a 3mm diameter rust-free steel needle to pierce the center of the largest surface of the battery cell at a speed of 2m / min and maintain it for more than 1h.
[0096] Cycle test: Place the battery cell in a 20℃±5℃ environment for 120 minutes, charge it at a constant current of 0.5C to the limit charging voltage, then charge it at a constant voltage until the current drops to 0.025C and stop charging; leave it for 10 minutes, then discharge it at a current of 1C to 3.0V. Repeat the above steps 300 times.
[0097] The test results are shown in Table 1:
[0098] Table 1
[0099]
[0100] As can be seen from Table 1, from Examples 1-9, the MD thermal shrinkage rate of the composite diaphragm of the present invention at 130°C for 1 hour can reach less than 3.0%, the TD thermal shrinkage rate can reach less than 1.2%, the 3C / 0.2C discharge rate can reach more than 96.2%, the needle puncture pass rate is more than 70%, and the thickness expansion rate after 300 cycles can reach less than 5.6%.
[0101] By comparing Example 1 with Examples 4-5, it can be seen that in the composite diaphragm of the present invention, the thickness of the solid electrolyte layer will affect its performance. When the thickness of the solid electrolyte layer is controlled at 1μm to 3μm, the performance of the composite diaphragm is better. If the thickness of the solid electrolyte layer is too large, the spatial tortuosity of the diaphragm increases, the air permeability deteriorates, the air permeability value increases, the lithium ion transmission distance increases, the transmission difficulty increases, and the rate performance deteriorates; if the thickness of the solid electrolyte layer is too small, the solid electrolyte cannot form a three-dimensional conductive network.
[0102] By comparing Example 1 with Examples 6-7, it can be seen that in the composite diaphragm of the present invention, the thickness of the inorganic ceramic layer will affect its performance. When the thickness of the inorganic ceramic layer is controlled at 1μm to 3μm, the performance of the composite diaphragm is better. If the thickness of the inorganic ceramic layer is too large, the accumulation of the ceramic layer will cause the air permeability of the diaphragm to deteriorate, affecting the rate performance, and if the thickness of the diaphragm is too large, it will affect the overall energy density of the battery cell. If the thickness of the inorganic ceramic layer is too small, the heat resistance of the diaphragm will decrease, the thermal shrinkage rate of the diaphragm will increase, and the risk of battery short circuit will increase, which is not conducive to safety performance.
[0103] By comparing Example 1 with Examples 8-9, it can be seen that the provision of a rubber coating layer on both sides of the composite separator in the present invention can increase the hardness of the battery, inhibit cyclic deformation, and improve the safety performance and high temperature resistance of the battery.
[0104] By comparing Example 1 with Example 10, it can be seen that the non-woven fabric material used in the present invention has the advantages of high temperature resistance and high porosity. In addition, due to its three-dimensional pore structure, it can effectively avoid the short circuit phenomenon caused by needle puncture and improve the liquid retention rate. Its high porosity can provide more ion channels, reduce DCR, and support high-rate charge and discharge.
[0105] By comparing Example 1 and Comparative Examples 1-2, it can be seen that different types of composite layers are arranged on both sides of the composite diaphragm of the present invention, the solid electrolyte layer can assist ion transport, the inorganic ceramic layer has excellent thermal stability and dimensional integrity at high temperatures, and plays a supporting role in maintaining the diaphragm structure at high temperatures, and the inorganic ceramic layer has greatly improved anti-shrinkage properties, and better mechanical properties and safety.
[0106] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A composite diaphragm, characterized in that: The composite diaphragm comprises a base membrane and a solid electrolyte layer and an inorganic ceramic layer respectively arranged on both side surfaces of the base membrane.
2. The composite diaphragm according to claim 1, characterized in that: The base film comprises a nonwoven fabric; Preferably, the structure of the base film includes a three-dimensional structure; Preferably, the three-dimensional structure is composed of cross-linked linear PET cellulose; Preferably, the diameter of the linear PET cellulose is 0.2 μm to 0.8 μm; Preferably, the base film has a thickness of 10 μm to 20 μm; Preferably, the air permeability of the base film is 15 Sec / 100cc to 20 Sec / 100cc.
3. The composite diaphragm according to claim 1 or 2, characterized in that: The material of the solid electrolyte layer includes solid electrolyte particles and a first binder; Preferably, the solid electrolyte particles include LATP; Preferably, the mass ratio of the solid electrolyte particles to the first binder is (70-90): (10-30); Preferably, the median particle size D50 of the LATP is 500nm to 1500nm; Preferably, the first binder comprises polyacrylate; Preferably, the thickness of the solid electrolyte layer is 1 μm to 3 μm.
4. The composite diaphragm according to any one of claims 1 to 3, characterized in that: A first glue coating layer is also provided on the side of the solid electrolyte layer away from the base film; Preferably, the first adhesive layer includes a PMMA adhesive layer and / or a PVDF adhesive layer; Preferably, the thickness of the PMMA coating layer is 0.2 μm to 0.8 μm; Preferably, the thickness of the PVDF coating layer is 1 μm to 2 μm.
5. The composite diaphragm according to any one of claims 1 to 4, characterized in that: The inorganic ceramic layer includes inorganic ceramic particles and a second binder; Preferably, the mass ratio of the inorganic ceramic particles to the second binder is (5-15): (85-95); Preferably, the inorganic ceramic particles include alumina and / or boehmite ceramics; Preferably, the second binder comprises polyacrylate; Preferably, the thickness of the inorganic ceramic layer is 1 μm to 3 μm.
6. The composite diaphragm according to any one of claims 1 to 5, characterized in that: A second coating layer is also provided on the side of the inorganic ceramic layer away from the base film; Preferably, the second adhesive coating layer includes a PMMA adhesive coating layer and / or a PVDF adhesive coating layer; Preferably, the thickness of the PMMA coating layer is 0.5 μm to 1 μm; Preferably, the thickness of the PVDF coating layer is 1 μm to 2 μm.
7. A method for preparing the composite diaphragm according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: The solid electrolyte layer and the inorganic ceramic layer are respectively prepared on the surfaces of both sides of the base film by a wet coating process to obtain the composite diaphragm.
8. The preparation method according to claim 7, characterized in that: After preparing the solid electrolyte layer, coating the first glue coating layer on the solid electrolyte layer; Preferably, after the inorganic ceramic layer is prepared, a second glue coating layer is coated on the inorganic ceramic layer.
9. A battery, characterized in that: The battery comprises the composite separator according to any one of claims 1 to 6.
10. The battery according to claim 9, characterized in that The battery comprises a positive electrode and a negative electrode arranged on both sides of the composite diaphragm, and an electrolyte is also arranged in the battery; Preferably, the solid electrolyte layer of the composite diaphragm is close to the positive electrode side; Preferably, the inorganic ceramic layer of the composite separator is close to the negative electrode side.
Citation Information
Patent Citations
Composite lithium battery separator and preparation method therefor
CN110859053A
Ionic membrane, preparation method thereof and semi-solid electrolyte battery
CN112952296A